Kerangka Regulasi Pemenuhan Hak Pelayanan Kesehatan Lansia Melalui Community-Based Integrated Care Perspektif Welfare State - Esa Auli Maftukha; Arif Hidayat (CV Rewang Rencang, 2025)
The growing elderly population in Indonesia is not matched by integrated regulation ensuring the right to community-based healthcare. Although Law No. 13 of 1998 mandates elderly health services, its implementation faces policy fragmentation, absence of standards, and sustainable funding. This study aims to formulate a regulatory framework for implementing Community-Based Integrated Care using a welfare state perspective. A normative-juridical method with regulatory analysis was applied. Findings reveal the need for a Presidential Regulation integrating inter-ministerial coordination, national service standards, and a hybrid funding scheme to fulfill the mandate of Law No. 13 of 1998 and realize welfare state principles in Indonesia.